2018
DOI: 10.4236/as.2018.91002
|View full text |Cite
|
Sign up to set email alerts
|

Estrus Synchronization and Artificial Insemination with Fresh and Chilled Semen in Assaf Ewes

Abstract: This paper aims to study the efficiency of two short-term progestagen (FGA vs. MAP) + eCG treatments in estrus synchronization and artificial insemination (AI) with fresh or chilled semen in Assaf ewes fertility rate. All ewes received a subcutaneous implant of exogenous melatonin 45 days before been treated with short-term progestagens + eCG. By June 1 st , ewes were divided in two groups: half was treated with an intravaginal sponge impregnated with 20 mg of FGA and the other half with an intravaginal sponge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…However, it was lower than values obtained by Mekuriaw et al (2005) who reported pregnancy rates of 70.6 and 70.4% in Dorper sheep synchronized with MAP and FGA sponges respectively. Similarly Fornazari et al (2018) reported pregnancy rates of 76.5% in Assaf sheep synchronized with progestagen sponges. However, the current result was higher than value obtained by Olivera-muzante et al (2011) who reported a pregnancy rate of 51% synchronized with two doses of PGF2α 7 days apart and inseminated cervically with fresh semen.…”
Section: Oestrous Responsementioning
confidence: 90%
“…However, it was lower than values obtained by Mekuriaw et al (2005) who reported pregnancy rates of 70.6 and 70.4% in Dorper sheep synchronized with MAP and FGA sponges respectively. Similarly Fornazari et al (2018) reported pregnancy rates of 76.5% in Assaf sheep synchronized with progestagen sponges. However, the current result was higher than value obtained by Olivera-muzante et al (2011) who reported a pregnancy rate of 51% synchronized with two doses of PGF2α 7 days apart and inseminated cervically with fresh semen.…”
Section: Oestrous Responsementioning
confidence: 90%
“…Improving the reproductive quality of the livestock industry is one of the main objectives of veterinarians [1]. Basically, fixed time artificial insemination [2] and estrous synchronization followed by superovulation [3] are used top quality semen that preserved as a liquid [3] or frozen form [4]. However, sometimes, small ruminants tend to silent heat [5], so these techniques might need to determine the estrous using estrous detector.…”
Section: Introductionmentioning
confidence: 99%